(3GdcGed (B- (3aj GdCOHs - (3eMeO Hf jRjO Hf YHO GdCcHQ GdKeGdj GdCROj, GdeHQO , CHh GdYHGS,J (B286 (3g` s ((3eUWai GdYdhGfj s)
(3ChdgG (B:s
(3MOKfG CHhYKeGf SYjO Hf LGHQ, bGd(B: (3MOKfG CHhGdMSf GdCNaT GdfMhj, bGd(B: "(3bQF dj gPG GdcJGH s
(3BNQgG (B:s
(3aGdhba jNQLhf GdQShd hEjGce Cj hjNQLhfce dCf JDefhG HGddg QHce s
(3fSNI NGeSIs
(3hHChdgG JQLeI ddeDda efbhdI ef cJGH (B"(3TPQGJ GdPgH(B" (3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B114s
Keywords: (3GdCOHs